2020
DOI: 10.1002/med.21734
|View full text |Cite
|
Sign up to set email alerts
|

Small molecules regulating reactive oxygen species homeostasis for cancer therapy

Abstract: Elevated intracellular reactive oxygen species (ROS) and antioxidant defense systems have been recognized as one of the hallmarks of cancer cells. Compared with normal cells, cancer cells exhibit increased ROS to maintain their malignant phenotypes and are more dependent on the “redox adaptation” mechanism. Thus, there are two apparently contradictory but virtually complementary therapeutic strategies for the regulation of ROS to prevent or treat cancer. The first strategy, that is, chemoprevention, is to prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(75 citation statements)
references
References 421 publications
(836 reference statements)
0
70
0
Order By: Relevance
“…Targeting these characteristics has been recognized as potential therapeutic approaches to cancer prevention and treatment. Apart from these conventional approaches, utilization of dietary sources is gaining wider attention in regulating these crucial events associated with cancer progression (Rodriguez‐Mateos et al., 2014; Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting these characteristics has been recognized as potential therapeutic approaches to cancer prevention and treatment. Apart from these conventional approaches, utilization of dietary sources is gaining wider attention in regulating these crucial events associated with cancer progression (Rodriguez‐Mateos et al., 2014; Zhang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Since excess ROS levels could be cytotoxic ( 35 ), apoptosis was examined using Annexin V/PI double staining assay. A significant increase in the percentage of apoptotic cells was detected after HT treatment for 24 h in HCT-116 and SW620 cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This system plays a role in maintaining H 2 O 2 levels in cells via the conversion of H 2 O 2 to H 2 O. Trx contains two adjacent thiols in its reduced form that are converted to a disulfide bond in the oxidized form ( 39 ). The oxidized Trx is then recycled back into the reduced form by TrxR1 and NADPH ( 35 ). The present study demonstrated that HT could significantly inhibit both recombinant and cellular TrxR1 enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…We then explored the mechanism by which ONP induced HeLa apoptosis and showed selective inhibition of tumor cell growth. Considering that one of the biochemical characteristics of carcinoma cells is that they exhibit a higher level of oxidative stress than normal cells, and further stimulation by cytotoxic agents leads to preferentially induce tumor cell apoptosis 10,49 . We thus observed the changes in ROS levels in HeLa cells treated with ONP to validate the elevated oxidative stress level is the mechanism by which ONP selectively induces tumor cell apoptosis.…”
Section: Increasing Ros Accumulationmentioning
confidence: 99%
“…Alteration of redox homeostasis is a hallmark of cancer cells 10 . Thioredoxin reductase (TrxR) enzymes as a critical player in regulating cellular redox signaling are increasingly recognized as attractive targets for anticancer drugs [11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%